Roller bearing under high loaded oscillations: Life evolution and accommodation mechanisms. (July 2020) - Cavacece, F.; Frache, L.; Tonazzi, D.; Bouscharain, N.; Philippon, D.; Le Jeune, G.; Maheo, Y.; Massi, F.
Abstract: High loaded oscillating bearings are used on several industrial fields such as robotics, wind power, aeronautics and aerospace. These bearings are subjected to extremely high local contact pressures and relatively low oscillatory speed. In this work, endurance tests on commercial single row spherical roller bearings enable to propose a degradation scenario for the bearing lifecycle. Topographical analyses carried out at each phase of the bearing life allowed to understand the degradation evolution at the interface between the inner-ring raceway and rolling elements. The analysis of the experimental results, with the support of numerical stress analysis, led to the understanding of the involved accommodation mechanisms. Then, a comparison with the wear processes in deep-groove ball bearings is provided. Highlights: Roller bearings under high load oscillation are investigated and compared to ball bearings. The overall surface and damage evolution of roller bearings are analyzed. The competition between surface and subsurface accommodation mechanisms are highlighted. The role of the grease on the surface protection is analyzed.